Adjustment policies and development strategies in the Arab world - El-Naggar, Saʻid, 1920- (International Monetary Fund, 1987)
Of the seminar / Said El-Naggar -- Adjustment challenges and strategies facing Arab countries in light of recent experience and new initiatives / A. Shakour Shaalan. Comment / Izzadin Ibrahim Hassan -- Structural adjustment in selected Arab countries : need, challenge, and approaches / Parvez Hasan. Comment / Mohamed Hashim Awad -- The role of the fund and the World Bank in adjustment and development / Azizali F. Mohammed. Comment / Mahsoun Jalal -- Adjustment and development : the case of Egypt / Galal A. Amin. Comment / M. Said Nabulsi -- Adjustment and development : the case of Jordan / Jawad Anani. Comment / Elias Saba -- Adjustment and development : the case of Morocco / Bachir Hamdouch. Comment / Mohammed T. Sadik.